2020
DOI: 10.1093/mnras/staa3676
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Karma asteroid family

Abstract: The Karma asteroid family is a group of primitive asteroids in the middle part of the main belt, just at the outer edge of the 3J:1A mean-motion resonance. We obtained the list of the family members with 317 asteroids, and estimated that it was formed by the catastrophic disruption of a parent body that was between 34 and 41 km in diameter. Based on the V-shape method, age of the Karma family is estimated to be about 137 Myr. A detailed dynamical map of the region combined with numerical simulations allowed us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…This provides a unique opportunity for an outer main-belt group to deliver fragments directly to the ν 6 resonance and via the resonance to the near-Earth region. Similarly, Pavela et al (2021) found that the Karma family, a group of primitive asteroids located at the outer edge of the 3:1 MMR with Jupiter, which is about 140 Myr old, has been supplying some asteroids to the near-Earth region. Currently, there should be about ten family members larger than 1 km in diameter, and many more smaller objects, orbiting in near-Earth space.…”
Section: Families Delivering Fragments On Earthmentioning
confidence: 88%
See 1 more Smart Citation
“…This provides a unique opportunity for an outer main-belt group to deliver fragments directly to the ν 6 resonance and via the resonance to the near-Earth region. Similarly, Pavela et al (2021) found that the Karma family, a group of primitive asteroids located at the outer edge of the 3:1 MMR with Jupiter, which is about 140 Myr old, has been supplying some asteroids to the near-Earth region. Currently, there should be about ten family members larger than 1 km in diameter, and many more smaller objects, orbiting in near-Earth space.…”
Section: Families Delivering Fragments On Earthmentioning
confidence: 88%
“…From a family formation to the delivery of members into near-Earth space. The example shows a scenario for the Karma asteroid family after the work byPavela et al (2021)…”
mentioning
confidence: 99%
“…Hsieh et al (2020), 1 https://bitbucket.org/sigrimm/genga 2 https://sirrah.troja.mff.cuni.cz/yarko-site/tmp/dt/swift_rmvsy.html 3 https://rebound.readthedocs.io/en/latest/ - Došović et al (2020), Martin and Livio (2021), while for recent works based on orbit9 see e.g. Knežević (2020), Pavela et al (2021), Dermott et al (2021). Despite being extensively used, the Yarkovsky and YORP effects are not included in the mercury package.…”
Section: Introductionmentioning
confidence: 99%